Awareness and attitude of students and professors of medical sciences universities toward social determinants of health: Design and preliminary psychometrics of a questionnaire - Farzaneh Mohammadi; Mahmoud Keyvanara; Rahele Samouei (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND AND AIM: Considering the important role of universities in advancing educational, social, cultural, economic, and political affairs and given the significant and effective role of social determinants of health (SDH) in personal and social life, this study aimed to design a preliminary questionnaire to assess the awareness and attitude of students and professors of relevant medical sciences departments toward the SDH. METHODS: This is a descriptive survey study of the instrumentation type and is done on the students and professors of Isfahan and Kashan medical sciences universities in 2019. The content and face validity of the questionnaire were assessed. Cronbach's alpha coefficient and the correlation coefficient for each question as well as the total score of the questionnaire were reported for this attitude measurement questionnaire. The difficulty coefficient, optimum difficulty level, discrimination coefficient, and the relevant variance were calculated for every question in the awareness measurement questionnaire. RESULTS: The internal consistency of the questionnaire for the awareness toward the SDH for 15 questions was 0.742. This consistency was acceptable for 18 questions in the attitude measurement questionnaire after omitting two questions with not appropriate distinguishing ability. The difficulty level of the questions was relatively high. CONCLUSION: Given that no tool was observed in the search strategy to measure the SDH, therefore, the design and psychometrics of such a tool can be used to measure the awareness and attitude of the target audiences; since this tool had an acceptable validity and reliability at its initial stages, researchers are suggested to apply it for standardization in different academic societies.